Observación de lazos de histéresis en CuO - Bianchi, Ana Elisa (2016)
Hysteresis loops at room temperature have been observed and investigated in nanostructures and nanoparticles ofCupric Oxide (CuO) with same average grain size. Morphological and structural properties of the studied sampleswere characterized using x-ray diffraction (XRD) and scanning electron microscopy (SEM). Energy-dispersive X-rayspectroscopy (EDS) was employed to analyze the possible presence of impurities. Mean crystallite diameter sizeswere determined using Rietveld refinement analysis of the diffraction patterns. The results suggest that hysteresisloops morphology depend on the process to obtain each sample, which not only affect grain size, but also mayinduce anisotropic forms and residual microstrains.